2013
DOI: 10.1002/ange.201208851
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Cross‐Dehydrogenative Coupling of Heterocycles with Aldehydes

Abstract: Ein Spektrum von Heterocyclen wurde regioselektiv durch metallfreie dehydrierende Kreuzkupplung von Heterocyclen mit Aldehyden erhalten. Die durch eine hypervalente Iodverbindung vermittelte Reaktion läuft bei Raumtemperatur ab, hat ein breites Substratspektrum und erfordert keinen Feuchtigkeitsausschluss. Die Methode erwies sich als nützlich in hocheffizienten, einstufigen Naturstoffsynthesen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0
2

Year Published

2013
2013
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 99 publications
0
21
0
2
Order By: Relevance
“…[11] Recently, our group has employed azidyl radicals as intermediates in the cross-dehydrogenative coupling of heterocycles with aldehydes and unactivated alkanes. [12] The azidyl radicals were generated by oxidation of azides in the presence of hypervalent iodine(III) reagents at ambient temperature. [13,14] Intrigued by these results, we hypothesized that these azidyl radicals could be used for the azidoarylation of alkenes as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Recently, our group has employed azidyl radicals as intermediates in the cross-dehydrogenative coupling of heterocycles with aldehydes and unactivated alkanes. [12] The azidyl radicals were generated by oxidation of azides in the presence of hypervalent iodine(III) reagents at ambient temperature. [13,14] Intrigued by these results, we hypothesized that these azidyl radicals could be used for the azidoarylation of alkenes as well.…”
mentioning
confidence: 99%
“…Experiments with varying amounts of oxidant suggested that 1.2 equiv is required to achieve complete conversion of 1 a to 2 a with higher yield ( Table 1, entries 5-8). Although few solvents did not promote the desired transformation ( Table 1, entries 9 and 10), DCM was found to be superior with 91 % yield for 2 a (Table 1, entries [11][12][13][14]. Significant amounts of unreacted 1 a were observed when the amounts of PhI(OCOCF 3 ) 2 and TMSN 3 were decreased further (see the Supporting Information for details).…”
mentioning
confidence: 99%
“…More recently, Antonchick and co-workers demonstrated a graceful metal-free cross-dehydrogenative coupling method to access papaveraldine in high yield. [14] We reasoned that our method could also provide an alternative approach to access the desired natural products in just one step.…”
mentioning
confidence: 99%
“…Diese Methoden beruhen auf einer Kaskade von C-C-oder C-Psowie nachfolgenden C-C-Verknüpfungsreaktionen, katalysiert durch Übergangsmetalle bei typischerweise hohen Temperaturen. [12] Die Azidylradikale wurden durch Oxidation von Aziden in der Gegenwart von hypervalenten Iod(III)-Reagentien bei Raumtemperatur generiert. [10] Deshalb stellten wir fest, dass die Wahl von N-Arylacrylamiden als Plattform zur Untersuchung der beispiellosen Azidoarylierung von Alkenen in einer Kaskade von C-N und C-C-Bindungsbildungen resultieren würde.…”
unclassified
“…[11] Vor kurzem hat unsere Gruppe Azidylradikale als Intermediate in der gekreuzten dehydrierenden Kupplung von Heterocyclen mit Aldehyden und nichtaktivierten Alkanen verwendet. [12] Die Azidylradikale wurden durch Oxidation von Aziden in der Gegenwart von hypervalenten Iod(III)-Reagentien bei Raumtemperatur generiert. [13,14] Angeregt durch diese Befunde vermuteten wir, dass solche Azidylradikale auch in der Azidoarylierung von Alkenen eingesetzt werden kçnnten.…”
unclassified